2015
DOI: 10.1002/polb.23695
|View full text |Cite
|
Sign up to set email alerts
|

Polypropylene/layered double hydroxide nanocomposites: Synergistic effect of designed filler modification and compatibilizing agent on the morphology, thermal, and mechanical properties

Abstract: This work addresses the optimization of the morphology, thermal, and mechanical properties of polypropylene/ layered double hydroxide (LDH) nanocomposites. For this, the nanofillers were modified by a calcination rehydration process using two surfactants, sodium dodecylsulfate (SDS) and sodium dodecylbenzenesulfonate, respectively. The nanofillers were characterized at each step of the modification process by thermal gravimetry, X-ray diffraction, and Infra red spectroscopy. Furthermore, the impact of anionic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 55 publications
0
9
0
Order By: Relevance
“…The volume fraction of nanofillers f , chosen in the range 0–10%, is a parameter of the geometrical model. The disk thickness values e have been chosen in the range 0.6–2 nm to match the typical thickness values of the elementary platelets for the most common lamellar nanofiller types . The disk diameter D was varied between 100 and 500 nm.…”
Section: Finite Element Simulationsmentioning
confidence: 99%
“…The volume fraction of nanofillers f , chosen in the range 0–10%, is a parameter of the geometrical model. The disk thickness values e have been chosen in the range 0.6–2 nm to match the typical thickness values of the elementary platelets for the most common lamellar nanofiller types . The disk diameter D was varied between 100 and 500 nm.…”
Section: Finite Element Simulationsmentioning
confidence: 99%
“…Biohybrids of HTlc and biomolecules can be designed to carry or drop functional biomolecules in gene therapy and drug delivery . Many studies demonstrated their ability to form micro‐ and nanocomposites with improved mechanical properties . Nanocomposites based on Na‐CMC and HTlcs have already been proposed in the literature, but only a few examples exist.…”
Section: Introductionmentioning
confidence: 99%
“…Stearate‐coated compounds have been reported to show better processing behavior, increased elongation at break, and improved impact properties at the cost of tensile strength . Regarding PP/LDH composites, the most widely reported anionic modifier is the C12 surfactant dodecyl sulfate/dodecylbenzene sulfonate . PP/LDH polymer nanocomposites were found to exhibit improved thermal properties and enhanced Young's and storage moduli at a filler loading of 10 wt % .…”
Section: Introductionmentioning
confidence: 99%
“…30,31,33 Regarding PP/LDH composites, the most widely reported anionic modifier is the C12 surfactant dodecyl sulfate/dodecylbenzene sulfonate. 23,25,34 PP/LDH polymer nanocomposites were found to exhibit improved thermal properties and enhanced Young's and storage moduli at a filler loading of 10 wt %. 17 The addition of 3 wt % of LDHs increased the crystallinity of PP and the thermal stability of the nanocomposites and decreased flammability.…”
Section: Introductionmentioning
confidence: 99%